Effect Of Garlic Oil Supplementation On Egg Yolk Lipid Profile And Performance Of Jabalpur Colour Birds (Applied Biological Research, 2012)
The present study was aimed to assess the effect of garlic (Allium sativum) oil on egg-yolk lipid profile and the performance of adult  layer birds. Twenty four 40-weeks-old Jabalpur colour birds were fed on 4 dietary treatments (diet supplemented with 0, 250, 500 and 750  mg garlic oil kg-1) for 56 days. Birds in each group were caged  individually and egg production and weight recorded daily whereas  body weight and feed consumption were taken on 0, 14, 28, 42 and  56th day of feeding. The variation in egg-yolk total lipids, cholesterol,  triglycerides, egg production and body weight between intervals within treatment were highly significant (p
Keywords: Cholesterol; egg yolk; garlic oil; Jabalpur colour birds; total lipid; triglycerides